Exploring Women's Leadership Communication in Masculine Logistics Industry: A Qualitative Study in the Delivery Service Sector - Josephine Chalyzta Riduvan FN (Jogjakarta Communication Conference (JCC), 2026)
This research critically analyzes how women's leadership is constructed, interpreted, and negotiated within a male-dominated delivery service organization. Using a qualitative case study approach, this research aims to explore how female leaders build authority, gain acceptance, and manage power dynamics in a masculine work culture. The findings of this study indicate that women's leadership is shaped by emotional-relational communication practices that emphasize empathy, listening skills, and responsibility, but is often limited by patriarchal norms that influence employe perceptions and interactions. Female leaders employ adaptive strategies such as emotional management and relational network building to maintain their professionalism and legitimacy as leaders. The results of this study also confirm that women's leadership in the masculine sector is dynamic, but still negotiated and has the potential to shape a more inclusive communication culture. This research contributes to the study of organizational communication and gender by demonstrating how empathy-based leadership can challenge traditional hierarchies and promote more equitable and human-value-oriented communication practices.